The clinicopathological and prognostic value of CXCR4 expression in patients with lung cancer: a meta-analysis - Qiu, Liping; Xu, Yuanyuan; Xu, Hui; Yu, Biyun (BMC cancer, 2022)
Background The C-X-C chemokine receptor 4 (CXCR4) has been suggested to play an important role in several types of cancers and is related to biological behaviors connected with tumor progression. However, the clinical significance and application of CXCR4 in lung cancer remain disputable. Thus, we conducted a meta-analysis to investigate the impact of CXCR4 expression on survival and clinicopathological features in lung cancer. Methods Comprehensive literature searches were conducted in PubMed, Embase and Web of Science for relevant studies. We pooled hazard ratios (HRs)/odds ratios (ORs) with 95% confidence intervals (CIs) by STATA 12.0 to evaluate the potential value of CXCR4 expression. Results Twenty-seven relevant articles involving 2932 patients with lung cancer were included in our meta-analysis. The results revealed that CXCR4 expression was apparently associated with poor overall survival (OS) (HR 1.61, 95% CI 1.42-1.82) and disease-free survival (HR 3.39, 95% CI 2.38-4.83). Furthermore, a significant correlation with poor OS was obvious in non-small cell lung cancer patients (HR 1.59, 95% CI 1.40-1.81) and in patients showing CXCR4 expression in the cytoplasm (HR 2.10, 95% CI 1.55-2.84) and the membrane (HR 1.74, 95% CI 1.24-2.45). CXCR4 expression was significantly associated with men (OR 1.32, 95% CI 1.08-1.61), advanced tumor stages (T3-T4) (OR 2.34, 95% CI 1.28-4.28), advanced nodal stages (N > 0) (OR 2.34, 95% CI 1.90-2.90), distant metastasis (OR 3.65, 95% CI 1.53-8.69), advanced TNM stages (TNM stages III, IV) (OR 3.10, 95% CI 1.95-4.93) and epidermal growth factor receptor (EGFR) expression (OR 2.44, 95% CI 1.44-4.12) but was not associated with age, smoking history, histopathology, differentiation, lymphatic vessel invasion or local recurrence. Conclusion High expression of CXCR4 is related to tumor progression and might be an adverse prognostic factor for lung cancer. Keywords: CXCR4, Lung cancer, Clinicopathological features, Prognosis, Meta-analysis